PENINGKATAN KEMAMPUAN HAFALAN BACAAN SHOLAT ANAK USIA 6 TAHUN MELALUI METODE PEMBIASAAN - Ayuningrum, Desy (Fakultas Tarbiyah, Institut PTIQ Jakarta, 2018)
The study was conducted at Jalan Pondok Cabe 1 no 97, Pamulang Banten. The time allocation in the field was carried out from November to December 2016. The subject of the study was 1 child of B Kindergarten aged 6 years. Action research using Kemmis and Mc. Taggart. This design contains stages starting from planning, action, observation and reflection. Data collection uses assessment sheets, observations, field notes and documentation. Analysis of data using observations and tests of action with qualitative descriptive analysis based on the results of observation and reflection. The study was divided into three cycles, one cycle consisting of two weeks, the first cycle in the first week completing S at 36% then continued to increase in the second cycle of 72% and the third cycle reached 90%, from 11 memorization targets 10 memorization had been achieved.